Heat Resistance of Bacillus Spores at Various Relative Humidities - Reyes, Antolin L. (1981)
The thermal resistance characteristics of spores from strains of five different Bacillus species were determined in phosphate buffer and at relative humidities ranging from <0.001 to 100% in a closed-can system. Spores tested in the closed-can system showed a marked increase in heat resistance over those in phosphate buffer, with the greatest increases occurring at relative humidities between 1 and 50%. When estimates of the time to reduce the initial spore concentration 99.99% (F value) at eight different relative humidities were plotted against temperature, three different types of heat resistance profiles were obtained, with maximum resistances at relative humidities of 1, 7, and 30%. When the various strains of spores were heated at the relative humidity of their maximum heat resistance, their relative order of heat resistance was different from that seen in buffer. Spores from the soil isolate were most resistant under these conditions (F(121.1) = 99.5 h).